2017
DOI: 10.1007/s11102-017-0832-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical debulking of pituitary adenomas improves responsiveness to octreotide lar in the treatment of acromegaly

Abstract: Pituitary surgery alone was more effective than primary medical treatment (p = 0.006), and the combination of surgery followed by medical therapy was even more effective (p < 0.0001). Subjects treated with medical therapy after surgical debulking had a significant improvement in response rate compared to matched subjects treated with primary medical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…This is the first study that evaluates molecular predictors of response to SRLs after debulking surgery of invasive GH‐secreting pituitary tumours. Our data are in the line of other studies showing that surgical debulking improve biochemical response to first‐generation SRLs in patients with large GH‐producing adenomas 9‐13 . In addition, we have identified two molecular markers: Ki‐67 and RORC linked to the odds of response to SRLs after debulking surgery that could be useful in clinical prediction algorithms.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is the first study that evaluates molecular predictors of response to SRLs after debulking surgery of invasive GH‐secreting pituitary tumours. Our data are in the line of other studies showing that surgical debulking improve biochemical response to first‐generation SRLs in patients with large GH‐producing adenomas 9‐13 . In addition, we have identified two molecular markers: Ki‐67 and RORC linked to the odds of response to SRLs after debulking surgery that could be useful in clinical prediction algorithms.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, enhancing SRLs response could be very useful. Several studies have proved that surgical debulking of these tumours improves SRLs response 9‐13 . Consequently, the current general consensus is to perform surgical debulking even if surgical cure is unlikely, both to alleviate mass effect and to improve SRLs treatment response 14‐16 .…”
Section: Introductionmentioning
confidence: 99%
“…One of two patients who were not controlled before surgery became controlled when lanreotide was re-introduced following the operation (36). Similar results were obtained by a recent observational study (35).…”
Section: Surgical Debulking and Responsiveness To Srlssupporting
confidence: 72%
“…In addition to a decrease of tumour burden, the goal of surgery for large tumours is to decompress the optic apparatus and the pituitary gland, thereby optimising a potential radiosurgery target. Moreover, surgical debulking of GH-secreting pituitary adenomas improves the postoperative control by SRLs (34,35,36,37). The first study that assessed if debulking surgery improved the post-surgical outcome of SRLs given postoperatively showed that GH normalisation was achieved in 29% patients preoperatively and rose to 54% after debulking, whereas the effect on IGF-I was more impressive, rising from 46 to 78% with postoperative medical therapy (37).…”
Section: Surgical Debulking and Responsiveness To Srlsmentioning
confidence: 99%
“…Moreover, with better surgery coverage, a greater possibility of pharmacological control in cases with no curative perspective can also be expected, which would also result in savings. Even when it is not possible to completely remove a tumour due to anatomical reasons, the resection of all possible tumour tissue (debulking) promotes a better response to drug treatment, which could lead to the use of lower doses of somatostatin analogues and a reduction in costs of treatment [ 4 , 32 34 ].…”
Section: Discussionmentioning
confidence: 99%